2019
DOI: 10.1142/s0218348x1950004x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Temperature Time Series From Batch Sugarcane Crystallization

Abstract: Batch crystallization is an important process in many industries, for example, fine chemicals, foods, and pharmaceuticals. Monitoring of the main process variables is essential for process understanding, diagnosis, and for product quality control. It is known that temperature has a critical effect on crystallization. Temperature measurements from crystallization systems display fluctuations with apparently random and complex behavior. Fractal analysis of complex time series has received significant attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[ 22 ] Furthermore, several authors have reported that these methodologies applied to process data can associate the multiscale indexes variation with different phenomena characteristics of a system at a specific time scale. [ 23,24 ] This because the fractal analysis permits the detection of long‐range correlations embedded in a time series by the presence of one or more power‐law behaviours. [ 25 ] Besides, it is easy to implement, with low computational cost, and due to its robustness to noise measurements it is suitable for operation in harsh environments, which makes it an attractive technique for flow‐pattern identification in comparison with other statistic methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Furthermore, several authors have reported that these methodologies applied to process data can associate the multiscale indexes variation with different phenomena characteristics of a system at a specific time scale. [ 23,24 ] This because the fractal analysis permits the detection of long‐range correlations embedded in a time series by the presence of one or more power‐law behaviours. [ 25 ] Besides, it is easy to implement, with low computational cost, and due to its robustness to noise measurements it is suitable for operation in harsh environments, which makes it an attractive technique for flow‐pattern identification in comparison with other statistic methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, imagebased multiscale analysis generates delays due to its acquisition and processing. In that sense, Campos-Domı ´nguez et al [19] performed a study by processing time series acquired from a batch cooling crystallization process by applying the rescaled range analysis (R/S) method. Results in that paper show that at characteristic scales, it is possible to identify zones related to the different phenomena involved in the process.…”
Section: Introductionmentioning
confidence: 99%